2012
DOI: 10.3324/haematol.2011.056721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of outcomes in adolescents and young adults with chronic myelogenous leukemia treated with upfront tyrosine kinase inhibitor therapy

Abstract: BackgroundOutcomes in chronic myeloid leukemia have improved with tyrosine kinase inhibitor treatment. However, little is known about outcomes of chronic myeloid leukemia in adolescent and young adult patients. Design and MethodsWe reviewed all 468 chronic myeloid leukemia patients treated at our institution with tyrosine kinase inhibitors as initial therapy: imatinib (n=281), nilotinib (n=98) or dasatinib (n=89). ResultsMedian age was 47 years, median follow up 71 months and median treatment time with initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
80
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 55 publications
11
80
2
1
Order By: Relevance
“…The problem of children and adolescents, and also of young adults, is of particular concern. It is believed and recommended [165][166][167] that children must be managed and treated like adults, but specific data are limited and more information pertaining to these particular age groups is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of children and adolescents, and also of young adults, is of particular concern. It is believed and recommended [165][166][167] that children must be managed and treated like adults, but specific data are limited and more information pertaining to these particular age groups is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…There is also much scarcity of available literature on the characteristic, presentation, outcome in this age group, although it has been noted recently by many researchers that, they differ significantly from the much commonly affected elderly population. 7 Although in these two cases, reaching the diagnosis was easily possible, still recent increase in the incidence of CML is not in conformity with the existing experience of the clinicians in our country. This type of disease may pose as diagnostic dilemma for unsuspecting eyes.…”
Section: Discussionmentioning
confidence: 96%
“…They also found that in this age group, second generation tyrosine kinase inhibitors conferred a better outcome compared to imatinib with a higher rate of complete cytogenic response (CCyR). 7 The reason behind this could be explained by many biological or psychological factors, which are yet not researched . For example, in 41 patients taking imatinib, it was found that body weight was the only variable that was significantly related to imatinib clearance and body weight can frequently be a rapidly changing parameter in many adolescents and young adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rick Proschmann, 1 Christoph Baldow, 1 Tino Rothe, 1 Meinolf Suttorp, 2 Christian Thiede, 3 Josephine T. Tauer, 2 Martin C. Müller, 4 Andreas Hochhaus, 5 Ingo Roeder 1,6 and Ingmar Glauche …”
mentioning
confidence: 99%